Pengaruh Konsentrasi Sari Buah Semu Jambu Mete (Anacardium occidentale L) terhadap Daya Terima Produk Sport Gel - Argadi, Ray Setha Sparis; Budiono, Irwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Cashew apple can be processed into food or beverage products such as jam, syrup, jelly and others. Sport gel is a sports drink product. The purpose of this study was to determine the effect of the concentration cashew apple juice on the acceptability of sports gel products. Methods: This research method uses complete randomized design. The ratio of cashew apple to water is given 1:0, 1:1, 1:2 and 1:3. Then a hedonic test was carried out to determine the acceptability of the sport gel using a questionnaire taken from 30 untrained panelists. The Somogyi-Nelson test is used to determine the total sugar content. Analysis of hedonic test data using the Kruskal-Wallis test and continued the Mann-Whitney test. Analysis of total sugar data using the Kruskal-Wallis test. Results: Hedonic test results p values = 0.000 (taste), 0.303 (aroma), 0.469 (texture), and 0.393 (color). Mann-Whitney's follow-up test results were p values = 0.000 (F0 and F1), 0.004 (F0 and F2), 0.002 (F0 and F3), 0.000 (F1 and F2), 0.000 (F1 and F3), 0.797 (F2 and F3). The result of the total sugar test p value = 0.083. Conclusion:The concentration of cashew apple juice only affects the acceptability in the taste aspect and does not affect the total sugar content of the cashew apple sport gel.